Costly immunometabolic remodelling in disused muscle buildup through physical exercise - Padilha, Camila S. [UNESP]; Figueiredo, Caique [UNESP]; Deminice, Rafael; Krüger, Karsten; Seelaender, Marília; Rosa-Neto, José Cesar; Lira, Fabio S. [UNESP] (Wiley, 2022)
The mechanisms underlying the immunometabolic disturbances during skeletal muscle atrophy caused by a plethora of circumstances ranging from hospitalization to spaceflight missions remain unknown. Here, we outline the possible pathways that might be dysregulated in such conditions and assess the potential of physical exercise to mitigate and promote the recovery of muscle morphology, metabolism and function after intervals of disuse. Studies applying exercise to attenuate disuse-induced muscle atrophy have shown a pivotal role of circulating myokines in the activation of anabolic signalling pathways. These muscle-derived factors induce accretion of contractile proteins in the myofibers, and at the same time decrease protein breakdown and loss. Regular exercise plays a crucial role in re-establishing adequate immunometabolism and increasing the migration and presence in the muscle of macrophages with an anti-inflammatory phenotype (M2) and T regulatory cells (Tregs) after disease-induced muscle loss. Additionally, the switch in metabolic pathways (glycolysis to oxidative phosphorylation [OXPHOS]) is important for achieving rapid metabolic homeostasis during muscle regeneration. In this review, we discuss the molecular aspects of the immunometabolic response elicited by exercise during skeletal muscle regeneration. There is not, nevertheless, consensus on a single optimal intensity of exercise required to improve muscle strength, mass and functional capacity owing to the wide range of exercise protocols studied so far. Despite the absence of agreement on the specific strategy, physical exercise appears as a powerful complementary strategy to attenuate the harmful effects of muscle disuse in different scenarios.